EMIZIKLI AYOLLAR SOG‘LOM OVQATLANISHINING DOLZARB MUOMMOLARI - Baratova, Shoxsanam (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
EMIZIKLI AYOLLAR SOG‘LOM OVQATLANISHINING DOLZARB MUOMMOLARI